A Brief History of Inquiry: From Dewey to Standards - Barrow, Lloyd (Journal of Science Teacher Education, 2006)
This paper describes how interpretations of inquiry have changed during the 20th Century. These multiple meanings have resulted in (a) confusion among K-12 teachers of science and (b) various interpretations by science teacher educators. Suggestions are provided for preservice programs (both science and methods courses), professional development for new and veteran teachers of science, and science education community to reach consensus about what is inquiry.